2002
DOI: 10.1190/1.1451622
|View full text |Cite
|
Sign up to set email alerts
|

Seismic monitoring of fluid fronts: An experimental study

Abstract: Seismic signatures of time-dependent reservoir processes, necessary for the interpretation of 4-D seismic data, are still insufficiently described. This experiment was designed to monitor fluid-front movements and saturation changes and to identify the related seismic signatures.Ultrasonic P-and S-wave transmission and reflection measurements were used to monitor the waterflooding of a porous sandstone. The sandstone was flooded in steps by filling a tank in which the room-dry cubic (50-cm side) block of rock … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 18 publications
1
16
0
Order By: Relevance
“…Whereas the relationship between the fluid front position and the onset of velocity decrease could be explained by taking into account the size of the Fresnel clearance zone [ Spetzler and Snieder , ], no explanation was found for the decoupled evolution of P wave amplitude and velocity. It was concluded that the P wave amplitude (related to the P wave attenuation) is more sensitive to fluid substitution processes than the P wave velocity, in agreement with the results of Wulff and Mjaaland [].…”
Section: Introductionsupporting
confidence: 87%
See 1 more Smart Citation
“…Whereas the relationship between the fluid front position and the onset of velocity decrease could be explained by taking into account the size of the Fresnel clearance zone [ Spetzler and Snieder , ], no explanation was found for the decoupled evolution of P wave amplitude and velocity. It was concluded that the P wave amplitude (related to the P wave attenuation) is more sensitive to fluid substitution processes than the P wave velocity, in agreement with the results of Wulff and Mjaaland [].…”
Section: Introductionsupporting
confidence: 87%
“…As the elastic properties of reservoir rocks are highly sensitive to the nature of the fluids saturating the pore space [ Mavko et al ., ; Rasolofosaon and Zinszner , ], remote seismic monitoring has been proposed as a tool to characterize fluid substitution processes in reservoirs [ Rasolofosaon and Zinszner , ]. Successful laboratory studies were conducted by Wulff and Mjaaland [] looking at reflected seismic waves in a block of sandstone flooded by water and by [ Stanchits et al ., ] in fluid injection experiments with acoustic emissions recording and ultrasonic monitoring. Recently, David et al .…”
Section: Introductionmentioning
confidence: 99%
“…The room‐dry sample is placed in a container that holds 5 mm of water. While the water is infiltrating into the pores of the sandstone by capillary pressure [ Wulff and Mjaaland , 2002], the water level in the container is kept constant at 5 mm. When the water front is rising from 5 mm to 10 cm, we repeat the ultrasonic impulse response measurement for every 1 cm increase in water level in the sandstone.…”
Section: Monitoring Water Saturation In Berea Sandstonementioning
confidence: 99%
“…This allows one to monitor the rise of capillary fronts during imbibition tests. Both seismic velocities and attenuation are sensitive to the passage of fluid fronts [14]. In the following we present the experimental device available in the rock physics lab at Cergy-Pontoise University, and we present some results obtained on two carbonate rocks.…”
Section: Ultrasonic Methods For the Detection Of Moving Capillary Frontsmentioning
confidence: 99%